Detection of ESBL and MBL in Acinetobacter spp. and their plasmid profile analysis - M. K. K., Fazlul; Rashid, Shah Samiur; Aizi Nor Mazila, Ramli; Ukaegbu, Chinonso Ishmael; M. H. M., Nazmul (Hashemite University, 2019)
The prevalence of extended spectrum β-lactamases (ESBLs), metalloβ-lactamases (MBL), and plasmid-mediated resistance is a severe threat to current lactam therapy leading to treatment failure. Therefore, in this research, an investigation has been conducted to study the presence of ESBL and MBL genes in Acinetobacter spp. and their relationship to antimicrobial resistance. Fifty Acinetobacter spp. isolates were collected from both pediatric and adult patients at Sungai Buloh Hospital, Kuala Lumpur, Malaysia. The Double Disk Synergy Test (DDST) and the E-test have been used to detect ESBL and MBL production. The plasmid was extracted using the Close and Rodriguez (1982) method with modification in addition to the QIAprep Spin Kit. Among the fifty Acinetobacter isolates, eleven (22%) were ESBL-positive, while none of the strains produced MBLs. Fourteen isolates were positive for a plasmid with an occurrence rate (POR) of 28 %. These fourteen isolates appeared to harbor one or more plasmids with a maximum of four plasmids. Four isolates had single plasmids, and five carried four plasmids, while four and one isolates had two and one plasmids respectively. The sizes of the plasmid DNA were found to range between 1.8 kb and 14 kb. This study emphasizes the problematic raising frequency of ESBL, MBL, and plasmid-mediated resistance. This awareness highlights an urgent need to prevent and control such bacteria